Changes in paternal perinatal depression and its predictors from third trimester of pregnancy to one-year post-partum: a longitudinal study - Kumiko Kido; Akemi Mitani; Yuko Uemura (Universitas Airlangga, 2024)
Introduction: Paternal depression is not as widely recognized as maternal depression. Studies in Japan have examined the factors associated with paternal depression, but these have been limited to specific regions rather than conducted on a nationwide scale. This study aimed to examine changes in paternal perinatal depression from the last trimester of pregnancy to one year postpartum. Additionally, we explored the relationship between paternal perinatal depression and fathers' feelings toward their infants. Methods: This study used a longitudinal design. We initially planned to collect data from over 384 cases based on sample size calculations, and successfully collected data from 494 men in the first survey. However, more than half of the participants dropped out in the second and subsequent surveys, resulting in 201 men completing the longitudinal survey over a one-year period. Results: The mean Edinburgh Postnatal Depression Scale, Japanese version (EPDS-J) score in the last trimester of pregnancy was 9.274 (95% confidence interval [CI] 8.413-10.134), which was the highest throughout the study period. The mean EPDS-J score was lowest at 3-5 months postpartum, with a score of 7.682 (95% CI 6.816-8.547). At all time points, occupational stress and partner relationships were associated with EPDS-J scores. Conclusions: Reducing paternal perinatal depression requires controlling for occupational stress and maintaining good marital relationships. The findings suggest that addressing work-life balance is crucial for Japanese fathers to enhance their whole-family well-being. Keywords: fathers, marital relationship, occupational stress, perinatal depression